"I miss my old life": Regretting motherhood on Mumsnet. (October 2020) - Matley, David
Highlights: Mumsnet Talk pages contained discourses of maternal regret from 2008 on. Digital media allow women to break the taboo of regretting motherhood. Expressions of regret as instances of after-the-fact agency. Mothers mourn their previous child-free lives. Responses to posts portray maternal regret as temporary or deficient. Abstract: One of the main criteria of being a "good mother" is evaluating motherhood as worthwhile and fulfilling. Yet in recent years there has been increased debate regarding women who regret having had children and who question the utilitarian rhetoric of childbirth and parenting. However, there is as yet little research into such counter-discourses of maternity and femininity in online environments. This study addresses this research gap by examining expressions of maternal regret in the Talk fora of Mumsnet, a UK-based parenting website. Focusing on stance-taking, it examines how women attempt to deal with regret and to create a sense of self between the binaries of good/bad mother discourses. The study contributes to an appreciation of the diversity of experiences of motherhood and the emotions and cognition that accompany them – ranging from mourning for one's previous life through guilt to acceptance – and highlights how digitally mediated communication functions as an arena in which women can break the taboo of maternal regret.